The therapeutic efficacy of 225Ac-DOTATATE in neuroendocrine tumors: a preliminary meta-analysis - Ma, Jiao; Ji, Yang; Yao, Zhihan; Yangqing, Jiangchu; Zhang, Chunyin (Frontiers in Oncology, 2025)
ObjectiveThis meta-analysis aims to evaluate the therapeutic efficacy and toxicity of 225Ac-DOTATATE in patients with metastatic neuroendocrine tumors (NETs).MethodsThis systematic review adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. PubMed and Embase were searched to identify studies that met the inclusion criteria. The primary endpoints were the evaluation of therapeutic efficacy through disease response rates (DRRs) and disease control rates (DCRs), and then toxicity is assessed. Additionally, a subgroup analysis was performed to evaluate the influence of prior 177Lu-peptide receptor radionuclide therapy (PRRT) on efficacy.ResultsThis meta-analysis included five studies involving a total of 153 patients. The results showed that the DRR following 225Ac-DOTATATE treatment was 52% [95% confidence interval (CI): 43%–61%], and the DCR was 88% (95% CI: 81%–94%). The incidence of hematological toxicity was low at 2% (95% CI: 0.00%–5%), with only two patients experiencing Grade I–II renal toxicity, and no Grade III–IV toxicities were observed. Subgroup analysis indicated that patients who had previously received 177Lu-PRRT treatment had a DRR of 51% (95% CI: 35%–66%) and a DCR of 90% (95% CI: 69%–100%), while 177Lu-naive patients had a DRR of 47% (95% CI: 1%–97%) and a DCR of 89% (95% CI: 72%–100%).ConclusionOur preliminary analysis shows that 225Ac-DOTATATE is an effective and safe treatment option for advanced metastatic NETs, significantly improving patients’ quality of life and demonstrating considerable disease control even in cases where other treatments have failed.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025633806.